2012
DOI: 10.1007/s11517-012-0924-6
|View full text |Cite
|
Sign up to set email alerts
|

Computational modeling of the human atrial anatomy and electrophysiology

Abstract: This review article gives a comprehensive survey of the progress made in computational modeling of the human atria during the last 10 years. Modeling the anatomy has emerged from simple "peanut"-like structures to very detailed models including atrial wall and fiber direction. Electrophysiological models started with just two cellular models in 1998. Today, five models exist considering e.g. details of intracellular compartments and atrial heterogeneity. On the pathological side, modeling atrial remodeling and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(129 citation statements)
references
References 241 publications
3
122
0
Order By: Relevance
“…Comprehensive review of such models can be found elsewhere [9]. However, even the most detailed three-dimensional models have not included accurate descriptions of fibre architecture in the atria.…”
Section: Comparison With Other Modelsmentioning
confidence: 99%
“…Comprehensive review of such models can be found elsewhere [9]. However, even the most detailed three-dimensional models have not included accurate descriptions of fibre architecture in the atria.…”
Section: Comparison With Other Modelsmentioning
confidence: 99%
“…A realistic 3D model of the atrial anatomy composed by 284,578 nodes [3] was used to simulate the atrial electrical activity by solving the atrial cell formulation proposed by Koïvumaki et al [4]. Fibrotic tissue was modelled by electrically disconnecting between 20% and 60% of the total nodes.…”
Section: Mathematical Modelsmentioning
confidence: 99%
“…Another important aspect by which the manuscripts are judged is the degree of innovation and the level of validation and also on thoroughness of the analysis. Hence, one may find in MBEC papers with a strong theoretical background such as the computation of the potential field [33], development of atrial fibrillation [10] and development of modeling framework for patientspecific computational hemodynamics [1]. This is not to say that a study on comparison of methods or instruments cannot make it into MBEC.…”
mentioning
confidence: 99%